KEGAWATDARURATAN KEJANG DEMAM PADA ANAK - Okti Sri Purwanti; Arina Maliya (Jurnal Berita Ilmu Keperawatan, 2008)
Children are subject that vulnerable to illness or diseases. They are tenderly sufferr from many diseases. One of them is fever convulsion. Fever convulsion have several early sign and symptom, for example : high body temperature, get fever, and convulsion. Fever convulsion is danger because can make some complication, dyspneu, restlessness, convulsion, takikardi, and altered tissue perfusion. Nurse as health care practitioner must aware pathofisology and diseases proses of fever convulsion. Nurse as provider nursing care must aware that fever convulsion is emergency case, so nurse giving nursing care with application emergency principle. Nursing proses is way of thingking and framework for giving nursing care, so nurse must must have them applicable in nursing care patient with fever convulsion. They must assess, diagnose, plan, implement dan evaluate in good manner